Osseointegrated Percutaneous Prosthetic System for the Treatment of Patients With Transfemoral Amputation: A Prospective Five-year Follow-up of Patient-reported Outcomes and Complications. Issue 16 (15th August 2019) - Brånemark, Rickard P.; Hagberg, Kerstin; Kulbacka-Ortiz, Katarzyna; Berlin, Örjan; Rydevik, Björn
Abstract : Introduction: Direct skeletal attachment of prostheses has previously been shown to improve patient-reported outcome (PRO) measures of individuals with transfemoral amputation (TFA) at 2-year follow-up. This prospective study reports the outcomes at 5-year follow-up. Methods: A total of 51 patients (55 legs) with TFA were included in a prospective study. Complications, success rate, and PRO measures were followed for 5 years. Results: The cumulative fixture survival rate at 5 years was 92%, and the revision-free survival rate was 45%. Thirty-four patients had 70 superficial infections. Eleven patients had 14 deep infections. Fifteen patients had mechanical complications. Four fixtures were removed (ie, one deep infection and three loosening). PRO measures showed significant improvements including more use of the prosthesis, better mobility, fewer issues, and improved physical health-related quality of life (all P < 0.0001) compared with baseline. Conclusion: Individuals with TFA at 5-year follow-up had significant improvement in PRO measures, but increases in deep infections and mechanical complications are concerning.